Le paysage urbain durable, une nouvelle utopie pour l’aménagement des villes ? - Cedissia About-de Chastenet (Projets de Paysage)
Does the engagement of the cities in a sustainable development policy produce a new urban forms and could it be at the origin of a change of the urban landscapes? How to define and characterize this landscape of a new kind combining the concepts of urban landscape and the sustainable development objectives? Which are the representations that are made of them the elected officials, the architects, the engineers or the users, who contribute, each one on their level, with the factory of the city? This article proposes some first brief replies to these questions while resting about talks carried out near actors of construction and urban planning in Paris.